2016
DOI: 10.2139/ssrn.2777383
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aspirations on Agricultural Innovations in Rural Ethiopia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In general, the recent extant studies suggest that gender (male), age, education, household size, farm size, off-farm income, access to extension services, access to credit and farmer association exert positive effects on the adoption of agricultural innovations such as inorganic fertiliser, improved crop variety and pesticides in some African countries, notably Nigeria, DR Congo, Uganda, Ghana, Cameroon and Ethiopia (Abdoulaye et al , 2014, 2015; Lambrecht et al , 2014; Obisesan, 2014; Afolami et al , 2015; Abate et al , 2016; Donkor et al , 2016; Mekonnen and Gerber, 2016; Abay et al , 2017; Alirah et al , 2018). For instance, studies have shown that male farmers are associated with higher adoption rates of agricultural innovations (namely, irrigation, pesticides and inorganic fertiliser) than their female counterparts in Nigeria, Ethiopia, Cameroon and Ghana (Obisesan, 2014; Donkor et al , 2016; Fosso and Nanfosso, 2016; Abay et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the recent extant studies suggest that gender (male), age, education, household size, farm size, off-farm income, access to extension services, access to credit and farmer association exert positive effects on the adoption of agricultural innovations such as inorganic fertiliser, improved crop variety and pesticides in some African countries, notably Nigeria, DR Congo, Uganda, Ghana, Cameroon and Ethiopia (Abdoulaye et al , 2014, 2015; Lambrecht et al , 2014; Obisesan, 2014; Afolami et al , 2015; Abate et al , 2016; Donkor et al , 2016; Mekonnen and Gerber, 2016; Abay et al , 2017; Alirah et al , 2018). For instance, studies have shown that male farmers are associated with higher adoption rates of agricultural innovations (namely, irrigation, pesticides and inorganic fertiliser) than their female counterparts in Nigeria, Ethiopia, Cameroon and Ghana (Obisesan, 2014; Donkor et al , 2016; Fosso and Nanfosso, 2016; Abay et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Other new research points at the important role aspirations or lack thereof play for innovation and technology adoption in agriculture. Mekonnen and Gerber (2016) find in Ethiopia that farmers with less aspiration adopt innovative practices less often, such as improved seeds and fertilizer. The upshot of this research is that innovation is endogenous to fundamental drivers, and not just a matter of transfer of knowledge and technology.…”
Section: Innovations From the Bottom Up With Farmersmentioning
confidence: 99%
“…To investigate the causal chain, we will test whether the videos aected awareness of modern inputs and improved agronomic practices, as well as whether they led to a change in the perceived protability of intensication investments. Some researchers have found evidence that videos featuring successful farmers aect aspirations and forward-looking behavior (Bernard et al 2015), in turn resulting in dierential technology adoption (Mekonnen and Gerber (2015)). Therefore, it may be that the videos in our study aected outcomes through inuencing attitudes and perceptions without directly altering knowledge related to technologies or expected returns.…”
mentioning
confidence: 99%